Green Bonds, Digital Finance on Green Finance Performance: The Mediating Role of GCG - Nur Rohmatillah, Ageng Widya; Rina Destiana (Journal of Science and Education (JSE), 2025)
This study aims to investigate the impact of green bonds, digital finance and good governance on green finance performance, with good governance also acting as a mediating variable. The study focuses on financial services institutions registered with the OJK in the period 2021-2023. A quantitative approach is used, employing multiple linear regression analysis and the Sobel test. The sample includes eight banks selected through purposive sampling due to the requirement to publish annual reports for the period 2021 to 2023. The results of this study suggests that green bond and Digital Finance have a significant positive impact on Green Financial Performance. In addition, good corporate governance successfully mediates the relationship between green bonds and green financial performance. However, the link between green financial performance and digital finance isn't affected by it.